Hypnotherapy compared to cognitive-behavioral therapy for smoking cessation in a randomized controlled trial - Batra, Anil; Eck, Sandra; Riegel, Björn; Friedrich, Sibylle; Fuhr, Kristina; Torchalla, Iris; Tönnies, Sven (Frontiers in Psychology, 2024)
Worldwide, more than eight million people die each year as a result of tobacco use. A large proportion of smokers who want to quit are interested in alternative smoking cessation methods, of which hypnotherapy is the most popular. However, the efficacy of hypnotherapy as a tobacco cessation intervention cannot be considered sufficiently proven due to significant methodological limitations in the studies available to date. The aim of the present study was to compare the efficacy of a hypnotherapeutic group program for smoking cessation with that of an established cognitivebehavioral group program in a randomized controlled trial. A total of 360 smokers who were willing to quit were randomly assigned to either hypnotherapy (HT) or cognitive-behavioral therapy (CBT) at two study sites, without regard to treatment preference. They each underwent a six-week smoking cessation course (one 90-minute group session per week) and were followed up at regular intervals over a 12-month period. The primary outcome variable was defined as continuous abstinence from smoking according to the Russell standard (West et al., 2005), verified by a carbon monoxide measurement at three measurement time points. The secondary Secondary outcome variables were was 7-day point prevalence abstinence at during the 12 months follow up and the number of cigarettes the non-quitters smoked per smoking day (smoking intensity). Generalized estimating equations were used to test treatment condition, hypnotic suggestibility, and other variablestreatment expectancy as predictors of abstinence. The two interventions did not differ significantly in the proportion of participants who remained continuously abstinent throughout the follow-up period (CBT: 15.6%, HT: 15.0%) and also regarding. However, CBT showed significantly higherthe 7-day abstinence rates at during the 12 months follow-upcompared to HT (CBT: 21.2%, HT: 16.7%). However, when controlling for hypnotic suggestibility, CBT showed significantly higher 7-day abstinence rates. . In terms of the continuous abstinence rates, iIt can be concluded that the efficacy of hypnotherapeutic methods for smoking cessation seem to be comparable to established programs such as CBT.